Delivering recovery focused mental health care in Ireland: implications for services and practice development. (22nd December 2014) - Shah, S. A.; Nolan, M.; Ryan, M.; Williams, J.; Fannon, D.
Abstract : Introduction: The recovery approach provides a key organising principle underlying mental health policy throughout the English speaking world with endorsement by agencies such as the World Health Organisation. In Ireland, personal recovery is one of the quality markers identified by users of mental health services and has become central to national mental health policy. Aim and objective: The aim of this study was to explore the implications for mental health services and professional practice arising from a structured investigation of what personal recovery means for people using specialist mental health services and the extent to which services support their individual recovery. Method: Ten service user participants in a service initiative were assessed using a novel measure based on an empirically based conceptual framework of recovery. The INSPIRE determines the level of recovery promoting support received from mental health staff and the quality of the supportive relationship as perceived by individual service users. Results: A consistent pattern of beliefs about recovery in keeping with national guidelines and the international literature was apparent. All respondents indicated that support by other people was an important part of their recovery with high levels of support received from mental health professionals. There was less consistent endorsement of the quality of relationships with professionals and recovery-oriented practice as perceived by participants. Conclusion: The findings are highly relevant to the development of recovery focused, clinically excellent services. Further work is needed to improve the process of translating recovery guidance into mental health practice.